Conversion of Cr(VI) to Cr(III) in Water Using Amino-Modified Ordered Mesoporous Silicas: Influence of the Functional Group Architecture - Rodríguez Castellón, Enrique (2025)
Two Nitrogen-modified mesoporous MCM-41 type silicas were synthesized by the sol-gel route andpost-grafting surface modification procedure, obtaining an aminopropyl-modified MCM-41(denoted MCM-41-N) and an aminoethyl-aminopropyl-modified MCM-41 (denoted MCM-41-NN).Hexavalent chromium removal from acidified water by adsorption and reduction to Cr(III) on thesolid mesophases was analyzed. The modified silicas were characterized by powder X-raydiffraction, infrared spectroscopy, nitrogen adsorption-desorption measurements at -196 °C, X-rayphotoelectron spectroscopy, 29Si solid state Nuclear Magnetic Resonance, and thermogravimetricanalysis. Both samples exhibited very high capacities for decreasing Cr(VI) concentrations in water,according to the Langmuir isotherm model: 129.9 mg·g-1 for MCM-41-N and 133.3 mg·g-1for MCM-41-NN. The chromium speciation in the supernatant after 24 h indicates that MCM-41-N had a higher capacity to reduce Cr(VI) to the less toxic Cr(III) species than MCM-41-NN: 92.9 % vs 72.5 % when the initial Cr(VI) concentration was 10 ppm. These differences were related to the different capacity of nitrogen atoms in MCM-41-N and MCM-41-NN to interact with the surrounding surface silanolswhich are required for the chemical reduction of the hexavalent species to take place, as evidencedby infrared spectroscopy and X-ray photoelectron spectroscopy analysis. Also, the Cr(III)/Cr(VI)atomic ratios on the solid’s surfaces were higher for MCM-41-N. These results highlight thecharacteristics that nitrogen atoms incorporated to silica matrices must possess in order to maximizethe transformation of Cr(VI) into the trivalent species, thereby reducing the generation of toxic wasteharmful to living organisms.